Arabisasi (Ta’rib) Istilah-istilah Ilmiah dalam Buku Pelajaran Biologi Kelas 3 SMA - Hilda Dimyati Asmara (Alfaz (Arabic Literatures for Academic Zealots), 2019)
Language is currently experiencing very rapid development, this has led to the birth of many new terms in the western world that effect between one language with another language, one of which is Arabic. One of the cuases of the birth of a new term because of the development of the science, technology and other sciences. So that arises the phenomenon of arabization or so-called ta’rib making Arabic adopt various foreign elements, either in the form of terms or words. Based on this background this research will discuss what words are contained in high school class 3 biology textbooks and how the method used in this study is a qualitative method of library study. The qualitative method is a research method that produces descriptive data in the form of written word from books related to research.